Numerical and experimental investigations of the micro-channel flat loop heat pipe (MCFLHP) heat recovery system for data centre cooling and heat recovery. (March 2021) - Weng, Chuangbin; Wang, Zhangyuan; Xiang, Jinwei; Zhao, Xudong; Chen, Fucheng; Zheng, Siming; Yu, Min
Abstract: This paper represented a dedicated study of the effects of coolant water flow on the performance of the micro-channel flat loop heat pipe (MCFLHP) heat recovery system using both theoretical and experimental methods. The MCFLHP heat recovery system is novel in the micro-channel flat plate evaporator of the loop heat pipe attached tightly to the heat generator of the IT equipment and the micro-channel flat plate condenser of the loop heat pipe installed outside the data cabinet, which realises the long distance heat removal from the inside of the data cabinet to the outside and reduces the energy consumptions in the data centre. This system adopted the separate evaporation and condensation structures, which were connected into a complete loop through vapour transmission line and liquid return line, and employed the heat exchange part and chiller part as the heat recovery devices. Taking into account the heat balances occurring in different parts of the system, a computer model was developed to predict the dynamic performance of the MCFLHP heat recovery system 8 at different coolant water flow rates when other working conditions were unchanged. Experiments were also conducted to validate results obtained from the simulation. Through comparison between the testing and modelling results, the model has been validated to be able to give a reasonable accuracy for predicting the performance of the MCFLHP heat recovery system. It was found that the heat recovery efficiency increased firstly and then decreased with the increase of the coolant water flow rate, and 300 L/h was the most optimal coolant water flow rate for the proposed system. The instantaneous heat recovery efficiency of the MCFLHP heat recovery system was maintained within 81–94% under the optimal coolant water flow rate when the system was running stably, and the average efficiency was at 84.06%. Highlights: Presented a dedicated study on the performance of the micro-channel flat loop heat pipe heat recovery system. Developed a heat transfer model to predict the dynamic performance. Conducted experiments to validate the established model. Obtained the optimised coolant water flow rate and the corresponding performance parameters. Compared with previous researches on heat recovery efficiency.